ANALISIS PEMBENTUKAN PORTOFOLIO OPTIMAL PADA BURSA EFEK INDONESIA (STUDI KASUS : SAHAM SEKTOR PERKEBUNAN, TELEKOMUNIKASI DAN KONSUMSI) - Salmah, Ninin Non Ayu (Universitas PGRI Palembang, 2012)
ABSTRAK This research discusses the forming of optimum portfolio on Indonesia Data Exchange with study case of the shares of plantation, telecommunication, and communication sectors. The samples of this research are PT. Astra Agro Lestari Tbk. , PT. Indosat Tbk. and PT. Indofood Sukses Makmur Tbk. The criteria to take the samples are the emiten which are included into the list of index LQ 45 in February 2007 until January 2010. The object of this research is the price of closing shares in which it was observed from January 2007 until 2009. The tools of analysis are the return, the risk of individual shares, and portfolio. The result shows that the portfolio formed from the shares of PT. Astra Agro Lestari Tbk. and PT. Indosat Tbk. is optimum and could be used as the option of investation. Kata Kunci : Return Saham, Risiko Saham, Portofolio Optimal